Mathematical analysis of SLIPR infectious model without vaccination: A case study of measles outbreaks - Fuaada Mohd Siam; Hanis Nas (Research and Social Study Institute, 2022)
: A five-compartment epidemiological model is analyzed to illustrate the dynamics of infectious diseases. In this model, the population is compartmented into susceptible, latent, infected, post-infection, and recovered. The model is a system of ordinary differential equations, where the stability is analyzed using Routh’s stability criterion. Two equilibrium points; disease-free and endemic equilibrium are stable but depends on the basic reproduction number. Derivation of the basic reproduction number is given using the next-generation method. This study ended by providing a case study of measles outbreaks before the effective implementation of the vaccine. The analysis of data fitting is done by using the Simulated Annealing minimization routine and the error value is 0.0406.